Italian experience on use of E.S.W. therapy for avascular necrosis of femoral head. (December 2015) - Russo, Sergio; Sadile, Francesco; Esposito, Roberto; Mosillo, Giuseppe; Aitanti, Emanuele; Busco, Gennaro; Wang, Ching-Jen
Abstract: Osteonecrosis (avascular necrosis) of the femoral head is a clinical disease due to a severe bone vascular alteration associated with intense pain and loss of joint function, with an incidence of 0.1% and unknown aetiology. Many classifications exist to describe it and in the final stages the patient will need a total hip arthroplasty. In the early stages, ESWT has given excellent responses. The Neapolitan school studied more than 600 patients who had very good results in I and II stages of Ficat and Arlet Classification, with an improve of outcomes in VAS and HSS scores. Moreover it has shown a complete restoration of the signal intensity of the femoral head in MRI. Highlights: Osteonecrosis of femoral head is a clinical disease due to a severe bone vascular disease. Associated to intense pain and loss of joint function, with incidence of 0.1% and unknown aetiology. Many classifications exist to describe it and say in final stages patient need THA. In early stages ESWT give excellent responses. Napolitan school studied more than 600 patients who had very good results in early stages.